2016
DOI: 10.1016/j.cropro.2016.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Bt-maize (MON810) against the stem borers Busseola fusca (Fuller) and Chilo partellus (Swinhoe) and its yield performance in Kenya

Abstract: A study was conducted to assess the performance of maize hybrids with Bt event MON810 (Bt-hybrids) against the maize stem borer Busseola fusca (Fuller) in a biosafety greenhouse (BGH) and against the spotted stem borer Chilo partellus (Swinhoe) under confined field trials (CFT) in Kenya for three seasons during 2013–2014. The study comprised 14 non-commercialized hybrids (seven pairs of near-isogenic Bt and non-Bt hybrids) and four non-Bt commercial hybrids. Each plant was artificially infested twice with 10 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
2
11
0
1
Order By: Relevance
“…This result is in line with studies conducted with MON 810 or Bt maize in different non-EU countries and regions that are subject to high pressure of certain maize insect pests. The conclusions consistently confirm an increased yield compared to the cultivation of conventional maize [39,[45][46][47].…”
Section: Discussionsupporting
confidence: 65%
“…This result is in line with studies conducted with MON 810 or Bt maize in different non-EU countries and regions that are subject to high pressure of certain maize insect pests. The conclusions consistently confirm an increased yield compared to the cultivation of conventional maize [39,[45][46][47].…”
Section: Discussionsupporting
confidence: 65%
“…Significance of insects and diseases observed on maize during the trials: Maize was sensitive to a diversity of insects as indicated by Steffey et al, 1999 andJean &Boisclair (2009). Lepidoptera are more likely to cause damage to maize (Ortega, 1988;Kfir, 1997;Tafera et al, 2016). Among Lepidopteran pests known in Cote d'Ivoire, only E. saccharina was found in this study.…”
Section: Discussionmentioning
confidence: 53%
“…Maize plants expressing the Bt toxin are also widely applied for control of the insect pests B. fusca and C. partellus (Mugo et al, ; Tefera et al, ). However, similar resistance problems as found for the fall armyworm have been found when applying the Bt technology for the control of B. fusca .…”
Section: Biotechnology a Tool To Limit Invasive Insect Pest Damagementioning
confidence: 99%